Sexual Violence Against Children And Criminal Sanctions Towards Actors Based On The System Of Indonesian Law - Monikasari, Shandra; Muhibbin, Moh.; Arief, Hanafi (International Journal of Law, Environment, and Natural Resources, 2023)
This study aims to describe how the criminal law regulates sexual violence in Indonesian positive law and to analyze how criminal sanctions for perpetrators of sexual violence against biological children are in Indonesian positive law. This research was conducted using normative legal research in the form of library research using three types of legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials, with a qualitative descriptive research analysis.The results of the study stated that the crime of sexual violence as a whole is regulated in the Criminal Code (KUHP), the Human Rights Law Number 39 of 1999, the Elimination of Domestic Violence Law Number 23 of 2004. And specifically against children as victims regulated in Law Number 35 of 2014 concerning Amendments to Law number 23 of 2002 concerning Child Protection. The results of other studies state that criminal sanctions for perpetrators of sexual violence in the Criminal Code against minors are formulated in Article 285 of the Criminal Code, namely imprisonment for a maximum of twelve years. Whereas in the Child Protection Act, imprisonment based on Article is a minimum of 5 (five) years and a maximum of 15 (fifteen) years and a maximum fine of Rp. 5,000,000,000.00 (five billion rupiah). Parents, guardians, caregivers of children, educators, or educational staff, then the penalty is added to 1/3 (one third) of the criminal threat as referred to in paragraph (1).